Financial Technology in Islamic Finance: Conceptual Foundations, Opportunities and Challenges - Ambarwati, Diana; Astri Yusniarti (Jurnal Internasional Ekonomi Islam, 2025)
Introduction: Almost every aspect of life can be addressed through technology, including the business and financial sectors. Financial technology (fintech) has emerged as a transformative innovation in Indonesia, presenting both opportunities and challenges. Sharia-based fintech, in particular, has attracted attention for its efforts to align financial innovation with Islamic principles. Objective: This article aims to outline the conceptions, opportunities, and challenges of fintech in the Indonesian context, with a particular focus on sharia fintech Method: A descriptive method is used. The descriptive approach is used to systematically describe facts, characteristics, and relationships within the fintech ecosystem without manipulating variables. Data are obtained from literature reviews, official regulations, and reports from relevant authorities, including Bank Indonesia, OJK, and DSN-MUI. Result: The Development of fintech in Indonesia presents a significant opportunity to encourage technology-based businesses, but also poses serious management challenges. Islamic fintech has received regulatory support from Bank Indonesia, DSN-MUI, and OJK to strengthen financial inclusion and smooth payment systems. However, obstacles such as DPS access, the length of the licensing process, and minimum capital requirements remain the primary barriers. Therefore, collaboration among all stakeholders is necessary to create a healthy and sustainable ecosystem for Islamic fintech.  Implication: The Development of Sharia fintech in Indonesia has the potential to strengthen financial inclusion and technology-based financial services. However, overcoming regulatory and economic challenges is essential to ensure the sustainability and growth of the sharia fintech ecosystem.